In Silico Analysis of miRNA-mRNA Binding Sites in Arabidopsis thaliana as a Model for Drought-Tolerant Plants - Yryszhan Zhakypbek; Aizhan Rakhmetullina; Zhigerbek Kamarkhan; Serik Tursbekov; Qingdong Shi; Fei Xing; Anna Pyrkova; Anatoliy Ivashchenko; Bekzhan D. Kossalbayev; Ayaz M. Belkozhayev (Plants)
Drought stress limits plant survival and yield in arid regions. Uncovering the molecular mechanisms of drought tolerance is key to developing resilient crops. This study used Arabidopsis thaliana as a model to perform an in silico analysis of miRNA–mRNA interactions linked to post-transcriptional drought response. Using the MirTarget program, 274 miRNAs and 48,143 gene transcripts were analyzed to predict high-confidence miRNA–mRNA interactions based on binding free energies (−79 to −129 kJ/mole). Predicted binding sites were located in the CDS, 5′UTR, and 3′UTR regions of target mRNAs. Key regulatory interactions included ath-miR398a-c and ath-miR829-5p targeting ROS detoxification genes (CSD1, FSD1); ath-miR393a/b-5p and ath-miR167a-c-5p targeting hormonal signaling genes (TIR1, ARF6); and the miR169 family, ath-miR414, and ath-miR838 targeting drought-related transcription factors (NF-YA5, DREB1A, WRKY40). Notably, ath-miR414, ath-miR838, and the miR854 family showed broad regulatory potential, targeting thousands of genes. These findings suggest the presence of conserved regulatory modules with potential roles in abiotic stress tolerance. While no direct experimental validation was performed, the results from Arabidopsis thaliana provide a useful genomic framework for hypothesis generation and future functional studies in non-model plant species. This work provides a molecular foundation for improving drought and salt stress tolerance through bioinformatics-assisted breeding and genetic research.